Possible Impacts on Nepalese Financial Service Sector Under WTO Provision - Malakar, Radheshyam (Socio-Economic Development Panorama, 2008)
By 2010 Nepal is going to open the Financial Service Sector (FSS) for the wholesale banking as per the World Trade Organization (WTO) commitments. Opening of the FSS brings both the positive as well as the negative impacts to the sector and to the economy. On the other hand, it may boost up the economy by properly channeling the capitals and provides the funds for the investment and on the other hand, the crisis in the sector is very harmful that can wind down the whole economy as well. At the present context, importance of FSS cannot be ignored to the economy. A poor and donor reliant country like Nepal, membership of WTO is not a matter of choice. The Capital Account Convertibility (CAC) regime is the pinnacle of the liberalization of FSS. There are some preconditioned for proceeding towards the full CAC regime to reap benefit from it. Socio-Economic Development Panorama, Vol. 1, No. 2(2007) pp. 71-82